Dez observações sobre mídia e violência - Rondelli, Elisabeth (Comunicação & Educação, 1996)
The article is about violence shown on TV programs. The author points out ten different approaches for the problem. Among them the most important ones are: the influente of violent programs on TV viewers; the strategy of getting more viewers and publicity by means of violent themes; relationship between young people and criminality; the midia and its capacity to juge the crime and the criminal and the stigmatization of poverty and the city of Rio de Janeiro as violent.